Craniocervical Pneumatization: Estimation of Prevalence and Imaging of Treatment Response. Issue 6 (July 2016) - Tomblinson, Courtney M.; Deep, Nicholas L.; Weindling, Steven M.; Lane, John I.; Scheibler, Linsey S.; Barrs, David M.; Hoxworth, Joseph M.
Abstract : Objective: Estimate the prevalence of craniocervical pneumatization (CCP) and describe successful treatment of this condition with clinical and radiologic correlation. Patients: Individuals with documented CCP on computed tomography (CT). Intervention(s): CT scans of the head, temporal bone, face, neck, and cervical spine. Cessation of habitual Valsalva maneuver (VM) and insertion of pressure-equalization (PE) tubes. Main Outcome Measure: The prevalence of CCP on CT examinations performed during two decades in a large academic healthcare system. Documentation of symptomatic and imaging improvement following treatment of CCP. Results: Radiology database review identified two cases of CCP out of a total of 636, 854 head and neck CT scans (0.00031%) or 43, 553 temporal bone CT scans (0.0046%). Both CCP patients were symptomatic (aural fullness, hearing loss, vertigo) and practiced habitual VM. One patient showed decreased CCP 4 months following cessation of VM, whereas the other patient improved symptomatically and demonstrated reversion of CCP to normal bone on magnetic resonance imaging (MRI) within 3 years following PE tube placement. Conclusions: Acquired CCP is exceedingly rare and, when successfully treated, reversion to normal bone may accompany symptom resolution.